(untitled) (ELang | An English Language Education Journal, 2017)
The paper is entitled “The Use of Describe and Draw Game For Improving Students’ Speaking Ability” (Pre-experimental Study Done In The First Grade of Vocational High School). This research focused on finding out whether or not Describe and Draw game can improve students’ speaking ability and to know whether or not the students like being taught Describe and Draw Game in improving students’ speaking ability. The subject of this research were first grade of SMK Taruna Cempakamulya. The Population of this research was X-AP of SMK Taruna Cempakamulya, with 30 students. In conducting this research, the researcher collected the data from the class that was carried out through pre-test, post-test, and questionnaire. The result of this research showed that improving students’ speaking ability by using Describe and Draw game was effective. It can be seen from the result of the t-test showed that in significance degree of 0.05, the value comparison is 14.643 > 2.045. It means that to (t-observation) is higher than tt (t-table). It could be said that t-test was higher than t-table. So, the Null Hypothesis (Ho) is rejected and Alternative Hypothesis (Ha) is accepted. It means that “The Use of Describe and Draw Game for Improving Students’ Speaking Ability” is effective. In other words Describe and Draw Game improve students’ speaking ability in the first grade of SMK Taruna Cempakamulya. And the result of questionnaire showed that more than half of the students agreed that using Describe and Draw improve their speaking ability. The students also gave positive response towards Describe and Draw Game for improving their speaking ability. Keywords: Describe and Draw, Game, Speaking.